Analisis Pengetahuan dan Sikap Masyarakat Desa Penglipuran, Bangli Terkait Upaya Pelestarian dan Konservasi Tumbuhan Upacara Ngaben Berdasarkan Tri Mandala - Ida Bagus Made Bramasta Wira bumi; Eniek Kriswiyanti -; Anak Agung Ketut Darmadi (Jurnal Pendidikan Biologi undiksha, 2021)
Bali is an island that rely on tourism as its main economy sources. Most of Bali’s tourism destination are in the form of Cultural tourism. Traditional ceremony as a part of culture in Bali held a main factor on supporting Bali’s tourism. Traditional ceremonies in Bali is variated started from giving birth, teenage ceremony, weeding and death. One of the most ceremony attract a lot of tourist each year to watch and visiting Bali is Bali’s Ngaben ceremony. Ngaben as one of the most touristic ceremony in Bali requires a lot of items such as plants and animals as it’s offering. To fulfill the need of plants for Ngaben, society need to culture and cultivated the plants in which needed for the ceremony. People of Penglipuran village, Bangli has divided their village into 3 main part called Tri Mandala. This division causing the plants that planted on each mandala or area are variated and diersified.However, there are no record about the knowledge and behaviour of Penglipuran village, Bangli in accordance to conservation and preservation of plant used in Ngaben ceremony. Hence, data about knowledge and behaviour of the conservation and preservation of plant used in Ngaben ceremony in Penglipuran, Bangli is essential to take futures step on the continuity of the ceremony and tourism. Therefore, the aim of this research is to know the knowledge and behaviour of people on Penglipuran village, Bangli in accordance to conservation and preservation of Ngaben ceremonial plant. This research using purposive sampling techinque in which 5 people were choosen to be key informan and 30 components of the society were choose to be given a quitioner. The result of the research found 31 species of plant used in Ngaben were found among 47 species of plants used in Ngaben at Penglipuran, Village Bangli. Peoples knowledge and attitudes regarding conservation and preservation of Ngaben ceremonial plant is considerably excellent with score for ach component on the society for the knowledge parameter as follows; government with score of 41,  village’s leader with score of 45.4, and 45,2 for society. Meanwhile, for behaviour, the score for government is 102, village’s leader is 97 and society is 93.